Foreign language learning using augmented reality environments: a systematic review - Schorr, Isabel; Plecher, David A.; Eichhorn, Christian; Klinker, Gudrun (Frontiers in Virtual Reality, 2024)
Augmented Reality (AR) is an advancing technology that has drawn the attention of educational material designers across various academic fields. However, few studies document the successes and setbacks of AR research in the language education sector. This review delves into educational research that employs AR for language training, examining the existing literature on this topic for development trends, benefits, challenges, and success patterns to derive design principles from them. In doing so, the paper covers 40 studies published between 2016 and 2023. The findings suggest that AR is mainly used for vocabulary acquisition with a clear trend toward applying marker-based technology and mobile devices. The design principles derived indicate that the potential of AR lies primarily in contextual learning, and that the technology alone may not satisfy students' needs in all aspects of language learning but should be used in combination with traditional teaching methods.